2016
DOI: 10.1007/s10899-016-9609-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Fear to Intervene with Problem Gamblers Related to Interveners’ Gender and Status? A Study with VLT Operators

Abstract: We assess how video lottery terminal (VLT) operators' self-perceive their ability to recognize a problem gambler, to what extent they are approached by problem gamblers seeking for assistance, how many detections and interventions they report, and the reasons they give for not intervening with clients who show signs of problem gambling. We also examine how these variables are related to the operators' gender and status in the establishment. 177 VLT operators anonymously completed a structured questionnaire at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pre and post-training questionnaires are systematically administered at the workshops to evaluate participants' satisfaction with the experience, and to investigate research questions. One study involving 177 VLT operators examined owners' and staff members' reluctance to intervene with clients who were showing signs of problem gambling (Tomei & Zumwald, 2016). In-keeping with the reports of a previous Australian inquiry (Hing & Nuske, 2011), the study showed that these frontline VLT operators are confident in their ability to identify the signs of problem gambling.…”
Section: Data From Lottery: Examining Problem Gambling Detection and mentioning
confidence: 90%
“…Pre and post-training questionnaires are systematically administered at the workshops to evaluate participants' satisfaction with the experience, and to investigate research questions. One study involving 177 VLT operators examined owners' and staff members' reluctance to intervene with clients who were showing signs of problem gambling (Tomei & Zumwald, 2016). In-keeping with the reports of a previous Australian inquiry (Hing & Nuske, 2011), the study showed that these frontline VLT operators are confident in their ability to identify the signs of problem gambling.…”
Section: Data From Lottery: Examining Problem Gambling Detection and mentioning
confidence: 90%